PENGARUH KONFLIK KERJA-KELUARGA DAN STRES TERHADAP PHYSICAL WITHDRAWAL BEHAVIOUR - Marga, Cok Putra Wibhisana; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2017)
Physical withdrawal behavior is the action someone takes when they are physically and psychologically already beginning to feel apart from the organization. Form of physical withdrawal behavior such as; absence, delay and turnover. This research was conducted at public transportation . The number of respondents is 52 employees. The analysis technique used is multiple linear regression. The result of analysis test in this research shows that work-family conflict has positive effect on physical withdrawal behavior. Occupational stress positively affects physical withdrawal behavior. The results of the analysis obtained in this study, it is expected organization can pay more attention to work-family conflict ando ccupational stress experienced by employees, so that the level of physical withdrawal behaviour perceived employees decreased.